The significance of practice in the training of conservator-restorers at the Faculty of Conservation and Restoration of Works of Art, Academy of Fine Arts in Warsaw - Krzysztof Chmielewski (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Extensive practice in the conservation work on original works of art should be one of the main objectives of the training of future conservator-restorers. The current curriculum at the Faculty of Conservation and Restoration of Works of Art, Academy of Fine Arts in Warsaw maintains a relative balance between theory and practice, but it is not flexible enough and being not yet fully adapted to today's challenges in the field of care of cultural heritage. It is going to be reformed in the coming years, with the new curriculum also meeting current requirements in the legislation on higher education in Poland.